Entrepreneurial network in Malaysia: Are there any differences across ethnic groups? - Minai, Mohd Sobri; Ibrahim, Yusnidah; Law, Kuan Kheng, (World Business Institute Pty Ltd, 2012)
The paper reveals interesting findings from the comparative study on entrepreneurial network of Malay and Chinese entrepreneurs in Malaysia conducted from July 2010 to December 2010. The two main ethnic groups, the Malays who are dominant in politic and the Chinese who traditionally are good in business, are the main ethnic groups in Malaysia and data from both ethnic groups is analysed from the total sample of 147 in which 59 are Malays and 88 are Chinese owner-managers.The findings show both ethnic groups have advantages and disadvantages over each other with respect to social, institutional and business networks